INFORMATION PROCESSING DEVICE, 3D MODEL GENERATION METHOD, AND PROGRAM (2021)
aA first-layer depth map generation unit (distance acquisition unit) of an encoding device (information processing device) acquires a first distance (d) between a projecting point (Q) and a first point (P) at which a straight line extending from the projecting point (Q) to a subject comes into contact with the subject, on the basis of a 3D shape of a surface of the subject. Furthermore, on the basis of the 3D shape of the surface of the subject, a second-layer depth map generation unit (distance acquisition unit) acquires a second distance (d) between the projecting point (Q) and a second point (P) from which the straight line extending through the inside of the subject from the first point (P) passes to the outside of the subject.